ESTRUTURA E DINÂMICA DO FUNCIONAMENTO PSÍQUICO DE MULHERES ENVOLVIDAS EM VIOLÊNCIA CONJUGAL REITERADA - Pacheco, Adriana das Chagas Oliveira (2015)
Despite campaigns to combat gender violence and legislation designed to promote increased safety of women involved in the phenomenon, studies performed have shown that many women abused by their partners, even after trying to split, returning to live with the perpetrators. Based on this information, the objective of this research was to study the structure and dynamics of psychic functioning of five women involved in repeated domestic violence. This is a clinical-qualitative study, whose participants were selected by convenience and are part of a group of women victims of domestic violence, attended by a non-governmental organization, with proceeding pending in a Criminal Court of São Paulo. Was used as research instruments with a semi-structured Interview Guide; the scale of the Brazilian Association of Market Research Institutes (ABIPEME); and the Object Relations Test Phillipson (TRO). The results show that the participants have weakened ego, poorly integrated and rigid superego, little indistinguishable from their destructive impulses and its internal persecutors, the result of introjections and deflections for the needy overseas. This mental dynamics developed from primary processes of very violent split, with a predominance of destructive impulses and the death drive on the life drive. In addition, it was noted that the participants remains predominantly in the paranoid-schizoid phase of development, unable to achieve properly the depressive position of repair, so they use primitive defense mechanisms to maintain mental balance as projective identification , denial, idealization and stalling. It is expected that the results of this research can assist in drawing up proposals for assisting women in repeated domestic violence situation.